THE PRINCIPAL'S ROLE IN IMPROVING TEACHER COMPETENCE - Didi Kriswanto; Enung Hasanah (Nurul Jadid University, Probolinggo, East Java, Indonesia, 2021)
This study aims to explore the role of principals in improving teacher competence and analyze the supporting and inhibiting factors of principals in improving teacher competence. This study uses a qualitative research approach in descriptive form. The subjects of this study were seven people consisting of the principal and six teachers with criteria based on years of service at elementary school Muhammadiyah Sagan. Data collection techniques include interviews, observation, and documentation. The validity of the data used triangulation of sources and methods. Data analysis activities include data reduction, data presentation, and conclusions. The results showed that the principal's role in improving teacher competence at elementary school Muhammadiyah Sagan was as an educator, manager, administrator, supervisor, leader, innovator, and motivator. Supporting factors are the willingness and enthusiasm of teachers, support from school coordinators, and adequate facilities and infrastructure. Meanwhile, the limiting factor is the limited budget of funds with many school needs, so the increase in teacher competence is minor. In addition, different teachers' different areas of expertise require other forms of training and cost a lot of money.